Les mécanismes légaux de lutte contre la cybercriminalité au Maroc - Roumate, Fátima (2018)
The topic of the present article is the cybercrime, which hinders the emergence and generalization of the use of ICTs in the professional, social and personal environment of people. It focuses on the legal mechanisms for fighting against cybercrime in Morocco. Morocco is seeking to enter a “knowledge economy”, which is an economy based on the widespread use of ICTs. The research brings together the efforts, difficulties, and inaccuracies that Morocco faces in regard to this phenomenon. It indicates and analyzes the actions implemented by different social factors in the field of legal, economic, governmental and international organizations, among others.